Diatrypella macrospora sp. nov. and new records of diatrypaceous fungi from Iran - Mehrabi, Mehdi; Hemmati, Roghayeh; Vasilyeva, Larissa N.; Trouillas, Florent P. (Phytotaxa, 2016)
Descriptions and illustrations are provided for six diatrypaceous species from Iran. Diatrypella macrospora is introduced as new to science. It differs from all other Diatrypella species by its larger ascospores. New records for the Iranian mycota include Cryptovalsa rabenhorstii, Eutypella citricola, Peroneutypa scoparia and Quaternaria quaternata. Descriptions and illustrations of microscopic characters, ITS sequence data and taxonomic notes are provided for these newly reported taxa.